A polypropylene composite material and its preparation method and application

By using a combination of black silica powder with specific components and polypropylene resin, the problem of dimensional instability of automotive interior materials in high temperature and high humidity environments is solved, and the high dimensional stability and mechanical properties of polypropylene composite materials are achieved. Reduced costs and opened up new uses for black silica.

CN114656716BActive Publication Date: 2025-01-10GUILIN FANGYIN NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011538628.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2025-01-10
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing automotive interior materials are prone to deformation in high temperature, high humidity and severe vibration environments, resulting in dimensional instability. Existing fillers such as talc powder are depleting and difficult to replace, affecting the mechanical properties and dimensional stability of the materials.

Method used

Using black silica powder with specific ingredients (mainly containing 14-20% CaO and 40-53% SiO2) instead of traditional fillers, a polypropylene composite material with excellent dimensional stability and mechanical properties is prepared by combining it with polypropylene resin. , avoiding the adjustment of polypropylene crystallinity and other additives.

Benefits of technology

The high dimensional stability and mechanical properties of polypropylene composite materials are achieved, reducing costs, and giving new uses of black silica, avoiding dependence on black pigments, meeting the needs of automotive interior and exterior decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114656716B_ABST
    Figure CN114656716B_ABST
Patent Text Reader

Abstract

The present invention discloses a polypropylene composite material suitable for car interior and bumper. By selecting black silica powder with special ingredients, the dimensional stability of the polypropylene composite material can be further improved compared with other fillers (such as talcum powder, calcium carbonate powder, metal particles, wollastonite powder and other granular fillers). When high-filled black silica powder is used, it can be used as a car bumper material; when the amount of black silica powder used is slightly lower, it can be used as a car interior.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polypropylene composite material and a preparation method and application thereof. Background Art

[0002] In the prior art, automobile interior decoration materials such as ABC pillars, door panel lower guards, door sills, and rear door guards are mostly made of polypropylene materials by injection molding. For black materials (bumpers and interior materials), the commonly used solution is black plastic made of polypropylene + toughening agent + talcum powder + black color powder (reinforced fiber needs to be added to the bumper material), which can be added with scratch-resistant agents for use as interior decoration. Another commonly used solution for automobile interior decoration materials is PP / PE alloy to improve the chemical resistance of PE.

[0003] When a car is driving, it will encounter severe vibration, high temperature, high humidity, temperature -10℃ (severe cold) and other environments, which will accelerate the deformation of the car's polypropylene composite material accessories. Even the accessories will undergo certain deformation during storage, which will have a certain impact on the car assembly. The bumper and interior materials of the car have high dimensional stability requirements. On the one hand, dimensional stability can reduce the abnormal noise caused by vibration during the driving of the car, and on the other hand, it also affects the appearance of the interior materials. The mainstream treatment method at this stage is to use raw materials with special processes and high costs. Some car manufacturers also use a large number of adhesives and fixing devices to tightly fix the car interior to the frame to prevent deformation and movement.

[0004] Chinese patent application CN109642065A discloses a polypropylene composition with good dimensional stability and excellent surface appearance, which is composed of a multiphase composition (including semi-crystalline polypropylene, ethylene / propylene copolymer, and ethylene-α-olefin copolymer. This patent mainly obtains good dimensional stability by changing the crystallization properties in the polyester matrix. Chinese patent application CN109776966A discloses a special material for low linear expansion coefficient polypropylene for bumpers, which is mainly obtained by a special preparation method: dissolving a titanate coupling agent in anhydrous ethanol to pretreat the glass fiber, mixing maleic anhydride grafted polypropylene with dodecane dodecylamine to obtain a compatibilizer, and then mixing the compatibilizer, polypropylene, polyester thermoplastic polyurethane, polyether thermoplastic polyurethane, talcum powder, and polyethylene wax, and then shearing and granulating with the pretreated glass fiber to obtain a product. Although the polypropylene composite material obtained by this scheme has extremely strong dimensional stability, it is hard to be used in car interiors because it is hard, and talcum powder is being depleted, and it is difficult for other existing fillers to replace talcum powder.

[0005] There are many Chinese patents that explore the effects of minerals on the dimensional stability of polyolefin compositions. Chinese patent application CN102875896A discloses the use of high-silicon talc powder and α-nucleating agent to fully crystallize the polypropylene material after the polypropylene composition is injection molded into parts, which can effectively reduce the linear expansion coefficient of the polypropylene composition and improve the dimensional stability. The use of inorganic fillers can control the subsequent crystallization of the polypropylene material without reducing the mechanical properties of the material, and can significantly improve the dimensional stability of the polypropylene composition under long-term cold and hot cycle conditions. However, it is common knowledge among those skilled in the art that high-silicon talc (silicon dioxide content greater than 62%) has higher mechanical properties than low-silicon talc-filled resin materials. There are few reports on how to use medium and low silicon fillers to prepare plastics with excellent performance.

[0006] Black silica is a silty carbonaceous layer stone with special engineering geological characteristics. It is widely distributed in Guilin, with good oxidation, high grade and natural pure black. Generally, black silica is a flaky structure with similar molecular content and performance characteristics to talcum powder, and the ore itself is pure black, high temperature resistant, and has a higher aluminum content than other black talc ores. The content of various components in black silica ores mined in different regions of Guilin varies greatly. After mechanical processing and crushing to a certain particle size, the original black silica can be used as a filling material for plastics, rubber and coatings; but due to the large span of chemical composition of black silica produced in different mines, it has a great impact on the performance of plastics after filling. Therefore, it is in line with national environmental protection policies to develop a method for the efficient application of black silica powders with different components. Summary of the invention

[0007] The object of the present invention is to provide a polypropylene composite material which has the advantage of good dimensional stability and can be used in car bumpers or car interiors.

[0008] The present invention is achieved through the following technical solutions:

[0009] A polypropylene composite material, comprising the following components in parts by weight:

[0010] 100 parts of polypropylene resin;

[0011] Black silica 1-50 parts;

[0012] Toughener 0-30 parts;

[0013] The black silica comprises the following components, which are mainly composed of 14-20% CaO and 40-53% SiO2 by weight percentage.

[0014] In addition to Al2O3 and SiO2, black silica mainly contains CaO, Fe2O3, K2O, MgO, MnO, Na2O, P2O5, TiO2, etc. It has been found through research that black silica ore is actually a complex mineral composition composed of multiple ores, and these components are mixed after millions of years of rock movement and extrusion. Black silica may also contain trace amounts of carbon, and the content varies depending on the mining area. Through sampling and testing in different black silica veins, five black silica ores with large differences in composition were found from many black silica samples. The content of each inorganic substance in black silica in the present invention is measured by the general rules of polycrystalline X-ray diffractometer method, and the detection equipment is X'Pert pro MPD powder X-ray diffractometer, and the detection is based on JY / T 009-1996 "General Rules for Polycrystalline X-ray Diffractometer Method", XRD semi-quantitative analysis.

[0015] The main differences in the composition of black silica ores mined in various places are the content of aluminum oxide, calcium oxide and silicon dioxide:

[0016] Black silica A: Al2O3 11-15%, CaO 17-19%, Fe2O3 2-4%, K2O 1.5-2.5%, MgO 1-2%, Na2O0.3-0.7%, SiO240-43%, TiO2 0.4-0.6%, and other components (abbreviated as LOI) as the balance.

[0017] Preferably, black silica B: Al2O3 7-9%, CaO 18-20%, Fe2O3 3-4%, K2O 1-2%, MgO 1-2%, Na2O0.1-0.3%, SiO2 45-48%, TiO2 0.2-0.4%, and other components (abbreviated as LOI) as the balance.

[0018] Black silica C: Al2O3 7-10%, CaO 14-17%, Fe2O32-3%, K2O 1-2%, MgO2-3.5%, Na2O 0.3-0.5%, SiO250-53%, TiO2 0.3-0.5%, and other components (abbreviated as LOI) as the balance.

[0019] Black silica D: Al2O3 21-22%, CaO 0.1-0.2%, Fe2O3 0.8-1%, K2O 2-3%, MgO 0.5-0.7%, Na2O 0.6-1%, SiO262-65%, TiO2 0.7-1%, and other components (abbreviated as LOI) as the balance.

[0020] Black silica E: Al2O3 17-19%, CaO 0.2-0.4%, Fe2O3 4-6%, K2O 2-3%, MgO 1-2%, Na2O0.5-0.8%, SiO261-64%, TiO2 0.5-0.9%, and other components (abbreviated as LOI) as the balance.

[0021] Black silica F: Al2O3 5-8%, CaO 9-12%, Fe2O31-2%, K2O 1.5-2.5%, MgO 3-4%, Na2O 0.2-0.5%, SiO264-67%, TiO2 0.1-0.3%, and other components (abbreviated as LOI) as the balance.

[0022] The experiment unexpectedly found that the silicon dioxide content in black silica ore A / B / C is lower than that in black silica ore D / E. However, the dimensional stability of black silica A / B / C filled with polypropylene is greater than that of polypropylene material filled with black silica D / E. It can be seen that high-silicon mineral powder does not necessarily produce polypropylene composite materials with high dimensional stability.

[0023] The addition of toughening agent is mainly to improve the toughness of composite materials, but if the amount of toughening agent added is too much, it will cause a decrease in dimensional stability. Generally, the amount of toughening agent added to automotive polypropylene composite materials is suitable for 3 / 8 / 15 parts. If special parts with strong toughness are required, a large amount of toughening agent can also be added. Of course, toughening agent can also be omitted according to the needs of the parts.

[0024] The polypropylene is at least one of homopolymer polypropylene and copolymer polypropylene; the melt index of the polypropylene is 8-100 g / 10 min (230° C., 2.16 kg). Copolymer polypropylene generally refers to propylene-ethylene copolymer.

[0025] The present invention does not explore the crystallization properties of polypropylene and / or the influence of the addition of nucleating agents on the overall crystallization properties of the material.

[0026] The toughening agent is selected from at least one of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, EPDM rubber and SEBS thermoplastic elastomer.

[0027] Optionally, the ethylene octene copolymer has a melt flow rate of 0.5 g / 10 min to 5 g / 10 min at 190 ° C and 2.16 kg, a melting point of ≥ 120 ° C, and a density range of 0.86 g / cm 3 -0.88g / cm 3 .

[0028] Optionally, the particle size of the black silica is in the range of 800-1500 mesh (about 5-15 microns). If extremely fine powder is required, it can also be ground to about 1.5 microns.

[0029] According to the requirements of the application scenario, reinforcing fibers can also be added to further improve the strength of the polypropylene composite material. By weight, 0-50 parts of reinforcing fibers are also included; the reinforcing fibers are selected from at least one of carbon fiber, glass fiber, and basalt fiber. Preferably, in an application environment requiring high strength, as a polypropylene composite material for automotive bumpers, high-filling reinforcing fiber filling is required (the reinforcing fibers can also be optionally modified and optimized, or a certain amount of compatibilizer can be added); while as a polypropylene composite material for automotive interiors, the filling amount of black silica and glass fiber is relatively small.

[0030] The invention also includes 0.1-10 parts by weight of at least one of an antioxidant, a lubricant, a pigment and a weathering agent.

[0031] The antioxidant includes a primary antioxidant which may be a hindered phenol antioxidant.

[0032] The lubricant is selected from at least one of stearate lubricants, fatty acid lubricants, and stearate lubricants; the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate; the fatty acid lubricant is selected from at least one of fatty acids, fatty acid derivatives, and fatty acid esters; the stearate lubricant is selected from at least one of pentaerythritol stearate.

[0033] Automobile interior polypropylene composite materials generally require certain flame retardant properties, and a certain amount of flame retardant can be added. By weight, 0-30 parts of flame retardant are also included; the flame retardant is selected from at least one of brominated flame retardants, phosphorus flame retardants, and flame retardant synergists.

[0034] The brominated flame retardant is selected from at least one of organic brominated flame retardants; the organic brominated flame retardant is selected from at least one of decabromodiphenylethane, tetrabromobisphenol A bis(2,3-dibromopropyl) ether, tris(tribromoneopentyl) phosphate, tris(2,3-dibromopropyl) isocyanurate, imine bromide, brominated epoxy resin, tris(tribromophenoxy) triazine, tetrabromobisphenol A, and tetrabromobisphenol S bis(2,3-dibromopropyl) ether.

[0035] The phosphorus-based flame retardant is selected from at least one of hypophosphites, phosphates, and polyphosphates; the hypophosphites are selected from at least one of aluminum hypophosphite, calcium hypophosphite, dimethyl aluminum hypophosphite, diethyl aluminum hypophosphite, and methylethyl aluminum hypophosphite; the phosphates are selected from at least one of triphenyl phosphate, resorcinol bis(diphenyl phosphate), bisphenol A-bis(diphenyl phosphate), and oligomeric aromatic phosphates; the polyphosphates are selected from at least one of ammonium polyphosphate, melamine phosphate, melamine pyrophosphate, and melamine polyphosphate.

[0036] The flame retardant synergist is selected from at least one antimony-containing compound and is mainly used in combination with a brominated flame retardant.

[0037] The preparation method of the above-mentioned polypropylene composite material comprises the following steps: polypropylene and toughening agent are uniformly mixed according to the ratio, extruded through a twin-screw extruder, reinforced fiber side-feeded (if reinforcing fiber is required), and extruded and granulated to obtain the polypropylene composite material.

[0038] The polypropylene composite material is mainly used for automobile interior decoration, automobile exterior decoration or automobile bumper.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention replaces traditional fillers (talcum powder, calcium carbonate, metal particles, wollastonite, calcite, etc.) with black silica of a specific composition (mainly containing CaO 14-20%, SiO2 40-53%) to improve the dimensional stability of polypropylene composite materials. It is not necessary to add other additives (nucleating agents, etc.) to improve the dimensional stability, nor is it necessary to examine the crystallinity of polypropylene. It is not only low-cost, but also provides a new high-value-added use for the abundant black silica. At the same time, the mechanical properties of the polypropylene composite material of the present invention can meet the needs of automotive composite materials. At the same time, due to the natural black color of black silica, it has a natural advantage in being applied to black automotive materials, avoiding the influence of the addition of black pigments / powders on other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 : Electron microscope photo of black silica A. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0043] The materials used in the present invention except black silica are derived from commercially available products:

[0044] Polypropylene: PP PDI078.

[0045] The black silica powder used in the embodiments and comparative examples is composed of the following table, which is 1250 mesh:

[0046] Black silica <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> MgO <![CDATA[Na2O]]> <![CDATA[SiO2]]> <![CDATA[TiO2]]> LOI A1 13.75 17.85 3.03 2.14 1.34 0.46 41.69 0.47 19.27 A2 14.41 18.55 3.60 1.47 1.06 0.56 42.77 0.51 17.07 B1 8.18 19.06 3.41 1.22 1.18 0.21 46.44 0.25 20.05 B2 7.66 18.12 3.71 1.35 1.52 0.14 47.92 0.32 19.26 C 8.62 15.26 2.42 1.5 2.75 0.43 51.11 0.37 17.54 D 21.33 0.11 0.88 2.61 0.59 0.76 64.37 0.88 8.47 E 17.82 0.33 5.28 2.73 1.46 0.64 62.5 0.69 8.55 F 7.31 10.54 1.39 1.76 3.85 0.24 66.81 0.26 7.84

[0047] Talc: particle size 1250 mesh.

[0048] Wollastonite: particle size 1250 mesh.

[0049] Calcite: particle size 1250 mesh.

[0050] Calcium carbonate: particle size 1250 mesh.

[0051] Toughener: POE LC565.

[0052] Antioxidant: Antioxidant 168.

[0053] Lubricant: TMP-6.

[0054] Glass fiber: CPIC ECS305K;

[0055] Flame retardant: Decabromodiphenylethane.

[0056] Flame retardant synergist: antimony trioxide.

[0057] Preparation method of polypropylene composite material of embodiment and comparative example: according to the proportion, polypropylene, black silica (or other fillers), toughening agent, antioxidant, lubricant (may also contain flame retardant) are added into a high-speed mixer and mixed evenly, and then put into a twin-screw extruder for extrusion granulation to obtain modified polypropylene filling material (extruder barrel temperature: first stage 210°C, second stage 215°C, third stage 210°C; screw aspect ratio is 25:1; screw speed is 400-600r / min).

[0058] Various performance test methods:

[0059] (1) The difference between the mold cavity size at 23℃±0.1℃ and the corresponding plastic part size measured at 23℃ and relative humidity of 50±5% for 24 hours after molding is calculated.

[0060] The shrinkage rate S is expressed by the following formula: S = {(D-M) / D} × 100% (1)

[0061] Where: S-shrinkage rate; D-mold size; M-plastic part size.

[0062] (2) Tensile strength: Refer to ISO 527 standard.

[0063] (3) Bending strength: refer to ISO178 standard.

[0064] Table 1: Distribution ratio of each group of polypropylene composite materials in Examples 1-6 (parts by weight)

[0065] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polypropylene 100 100 100 100 100 100 Black silica powder A1 10 20 30 30 40 - Black silica powder A2 - - - - - 40 Toughening agent 8 8 8 15 8 8 Flame retardants - - 10 - - - Flame retardant synergist - - 2 - - - Fiberglass - - - - 10 10 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Lubricants 0.2 0.2 0.2 0.2 0.2 0.2

[0066] Table 2: Distribution ratio of each group of polypropylene composite materials in Examples 7-9 (parts by weight)

[0067] Example 7 Example 8 Example 9 Polypropylene 100 100 100 Black silica powder B1 20 Black silica powder B2 20 Black silica powder C 20 Toughening agent 8 8 8 Antioxidants 0.2 0.2 0.2 Lubricants 0.2 0.2 0.2

[0068] Table 3: Distribution ratio of each group of comparative polypropylene composite materials (parts by weight)

[0069] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Polypropylene 100 100 100 100 100 100 100 Black silica powder D 20 Black silica powder E 20 Black silica powder F 20 talcum powder 20 Wollastonite 20 Calcite 20 Calcium carbonate 20 Toughening agent 8 8 8 8 8 8 8 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Lubricants 0.2 0.2 0.2 0.2 0.2 0.2 0.2

[0070] Table 4: Test results of various properties of the embodiments and comparative examples

[0071] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 S-shrinkage, % 1.0 0.8 0.7 0.8 0.5 0.5 Tensile strength, MPa 18 20 22 21 24 23 Bending strength, MPa 25 26 29 28 37 35

[0072] Table 4 continued:

[0073] Example 7 Example 8 Example 9 S-shrinkage, % 0.8 0.7 0.9 Tensile strength, MPa 21 22 21 Bending strength, MPa 27 27 26

[0074] Table 4 continued:

[0075] S-shrinkage, % Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 S-shrinkage, % 1.5 1.3 1.4 1.3 1.3 1.4 1.5 Tensile strength, MPa 22 22 21 18 17 15 23 Bending strength, MPa 27 28 27 23 25 22 26

[0076] It can be seen from Examples 1-5 that the increase of black silica powder can inhibit shrinkage, while the increase of toughening agent will increase the shrinkage rate.

[0077] From the comparison of Examples 2 / 7 / 8 / 9, it can be seen that black silica composition B is preferred.

[0078] It can be seen from Comparative Examples 1-3 that although the polypropylene composite material with a high silicon content has better reinforcement performance, its dimensional stability is not good enough.

[0079] It can be seen from comparative examples 4 / 5 / 6 / 7 that the addition of various powders improves the strength in different ways, but the dimensional stability is not as good as the black silica powder defined in the present invention.

Claims

1. A dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper, characterized in that: By weight, it is composed of the following components: 100 parts of polypropylene resin; Black silica 1-50 parts; Toughening agent 0-30 parts; Reinforcement fiber 0-50 parts; Flame retardant 0-30 parts; It also includes 0.1-10 parts of at least one of an antioxidant, a lubricant, a pigment, and a weathering agent; The composition of black silica is: Al2O3 7-9%, CaO 18-20%, Fe2O3 3-4%, K2O 1-2%, MgO 1-2%, Na2O 0.1-0.3%, SiO245-48%, TiO2 0.2-0.4%, other components balance; Or the composition of black silica is: Al2O3 7-10%, CaO 14-17%, Fe2O32-3%, K2O 1-2%, MgO2-3.5%, Na2O 0.3-0.5%, SiO250-53%, TiO2 0.3-0.5%, other components balance; The particle size range of the black silica is 800-1500 meshes.

2. The dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper according to claim 1, characterized in that: The composition of black silica is Al2O3 7-9%, CaO 18-20%, Fe2O3 3-4%, K2O 1-2%, MgO1-2%, Na2O 0.1-0.3%, SiO245-48%, TiO2 0.2-0.4%, and other components as the balance.

3. The dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper according to claim 1, characterized in that: The polypropylene is at least one of homopolymer polypropylene and copolymer polypropylene; the melt index of the polypropylene is 8-100 g / 10 min, 230° C., 2.16 kg.

4. The dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper according to claim 1, characterized in that: The toughening agent is selected from at least one of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, EPDM rubber and SEBS thermoplastic elastomer.

5. The dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper according to claim 1, characterized in that: The reinforcing fiber is selected from at least one of carbon fiber, glass fiber and basalt fiber.

6. The dimensionally stable polypropylene composite material for automobile interior, automobile exterior or automobile bumper according to claim 1, characterized in that: The flame retardant is selected from at least one of a brominated flame retardant and a phosphorus flame retardant.

Citation Information

Patent Citations

  • Polypropylene composition with good dimensional stability and preparation method and application thereof

    CN102875896A

  • Stiff propylene composition with good dimensional stability and excellent surface appearance

    CN109642065A

  • Special low-linear expansion coefficient polypropylene material for bumpers, and preparation method thereof

    CN109776966A

  • Modified chert powder and preparation method and application thereof

    CN110527141A